Improving Eighth Grade Students’ Listening Comprehension Through Dictogloss Technique - Nila Sahriyah; Hastini Hastini; Fadhilah Zamzam; Abd. Kamaruddin (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
This study investigates the effectiveness of the dictogloss technique in improving the listening comprehension of eighth grade students at MTs Muhammadiyah Al-Haq Palu during the 2024/2025 academic year. Employing a pre-experimental quantitative design, the study involved all 25 students from the target class as participants. Data were collected using pre-test and post-test instruments, each comprising 10 fill-in-the-blank and 10 multiple-choice questions focused on narrative texts as a test. Dictogloss technique was implemented as the intervention, where students listened to passages, took notes on key points, and collaboratively reconstructed the texts. Statistical analysis revealed a significant improvement in students’ listening comprehension, with the mean score rising from 51.40 (pre-test) to 75.00 (post-test). The Shapiro-Wilk test confirmed normal data distribution, and paired sample t-tests indicated the improvement was statistically significant (p < 0.05). The findings suggest that dictogloss not only improves students’ ability to recognize spoken words and understand main ideas but also increases engagement, vocabulary acquisition, and collaborative skills. The study concludes that integrating the dictogloss technique into classroom instruction is an effective strategy for improving listening comprehension among junior high school students learning English as a foreign language.